1901 Ariz. Sess. Laws 1253 - (:unkn) unknown (My University, 1901)
§ 392: Prohibited brandishing a deadly weapon in the presence of two or more persons, in a rude, angry, or threatening manner, or who unlawfully uses the same in any fight or quarrel. Violators guilty of a misdemeanor.
Keywords: BRANDISHING